2017
DOI: 10.3917/spub.175.0741
|View full text |Cite
|
Sign up to set email alerts
|

Eau potable, assainissement et risque de maladies diarrhéiques dans la Communauté Urbaine de Nouakchott, Mauritanie

Abstract: Therefore, exposure to diarrheal diseases through the prism of water and sanitation is a real public health problem that requires a systemic and integrated approach to improving environmental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
0
10
0
3
Order By: Relevance
“…These factors may explain the extremely high case fatality rates in pediatric patients hospitalized with diarrhea and respiratory diseases. In fact, according to a study conducted in 2012, 2150 people, including 1700 children less than five years of age, die each year from diarrhea in Mauritania, and 90% of these deaths are directly attributable to the poor quality of water, sanitation, and hygiene [ 14 ]. In addition, many patients present to the health system after a relatively high time lapse since the start of symptoms, as a result of difficult access to the health system, and also a low awareness of the urgency of these conditions, in the child population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors may explain the extremely high case fatality rates in pediatric patients hospitalized with diarrhea and respiratory diseases. In fact, according to a study conducted in 2012, 2150 people, including 1700 children less than five years of age, die each year from diarrhea in Mauritania, and 90% of these deaths are directly attributable to the poor quality of water, sanitation, and hygiene [ 14 ]. In addition, many patients present to the health system after a relatively high time lapse since the start of symptoms, as a result of difficult access to the health system, and also a low awareness of the urgency of these conditions, in the child population.…”
Section: Discussionmentioning
confidence: 99%
“…Primary healthcare facilities are insufficient. Recent studies conducted in Nouakchott reported that less than 44% of children were taken to a healthcare facility, and only 26% of households had access to safe drinking water sources, while 70% of the population had access to improved latrines [ 9 , 14 ]. The situation in rural areas is even worse.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that in our developing countries water-related diseases represent a real public health problem [13] [14]. The lack of drinking water and sanitation [15], as well as the low level of education of our populations, are the main causes. In addition, antibiotic resistance is becoming more and more frequent [16] [17].…”
Section: Discussionmentioning
confidence: 99%
“…L'influence des mal-adaptabilités biologiques en lien avec la qualité de l'eau semble se poser de façon récurrente dans les pays en développement. Dans ces pays, les populations sont confrontées au déficit des équipements d'accès à l'eau potable et au manque d'infrastructures sanitaires de gestions des déchets de qualité (Sy et al, 2017). La Côte d'Ivoire, un pays de l'Afrique de l'ouest est confrontée à cette réalité socio-environnementale (Angoua et al,2018).…”
Section: Méthodologie Matérielsunclassified